دور التسويق الفــيروسي في بناء الشُهرة غير المُشتراه للمُشروعات الناشئة في ليبيا دراســــة ميدانية على عينة من المشروعات الناشئة التجارية بمدينة طبرق نموذجاً (Economic studies journal, 2022)
First, the research aims to highlight the two concepts of viral marketing, and the concept of non-purchased Goodwill, The next goal of the research was to define the role viral marketing can play in building the non-purchased Goodwill for Startups in Libya.  The first goal was achieved by presenting a conceptual presentation of viral marketing, the concept of non-purchased Goodwill and the nature of the possible relationship between them; The research ended with a field study that served as the second goal, and was based on taking opinions in this regard, and the researcher relied on a sample of (25) individuals who answered the questionnaire as a main tool for data collection, which was analyzed by descriptive and inferential statistics (correlation coefficient), and accordingly it was reached For the following main result:         Viral marketing plays an important role in building non-purchased Goodwill for Libyan start-ups;, and contributes to this with an expected percentage of (R Square=77.6%), with an importance level of (0.004); Compared to a significant level (α =0.050).          The study recommends the following: The need for Libyan start-ups to adopt the concept of viral marketing and include it among the most important variables that control the building of non-purchased Goodwill .References• Andreas M.Kaplan Michael Haenlein,(2011)."Two hearts in three-quarter time: How to waltz the social media/viral marketing dance", Business Horizons Volume 54 , Issue 3, May–June 2011, Pages 253-263• Bampo, M., Ewing, M.T., Mather, D.R., Stewart, D. and Wallace, M. (2008). "The effects of the social structure of digital networks on viral marketing performance". Information Systems Research, 19 (3), 273–290.• Javi (October ,2018). "Goodwill: Meaning, Features and Types" , available online https://www.holded.com/blog/goodwill-meaning-features-types 25\9\2021-• Redmond, Jodee .(2020)."Disadvantages of Viral Marketing", available online at:https://business.lovetoknow.com/business-marketing-business-owner/disad vantages-viral-marketing. 27\12\2021-• Prabjot,(2017). "Goodwill: Meaning, Features, Types and Accounting", available online, https://www.yourarticlelibrary.com/accounting/goodwill/goodwill-meaning-features-types-and-accounting/5717530\10\2021-• Li, et al (2015), "What triggers sharing in viral marketing? The role of emotion and social feature", Conference: 19th Pacific Asia Conference on Information Systems (PACIS 2015). 19\12\2021-• Sukhraj Ramona,(2016)."The Advantages of Viral Marketing", available online at : https://www.impactplus.com/blog/the-advantages-of-viral-marketing Kaplan. Andreas and Heinlein. Michael. 3\11\2021-• Shaw Academy,( Jan 2020)." Advantages of Viral Marketing with Examples", available online at :https://www.shawacademy.com/blog/advantages-of-viral-marketing-with-examples/. 3\1\2021-• Skrop, John-Robert,( August 2005)." Source and Viral marketing several marketing concept as model for open source software to reach the critical mass for global bran awareness based on the example of TYPO3,University of Applied Science Kufstein ,Vienna .Gorman,M.(2020)," What Exactly Is Content Marketing" available online at : https://business.lovetoknow.
Keywords: viral marketing; non-purchased (earned) goodwill